Improving Writing Ability of Narrative Notes Using Constructivism Approaches Class V Students SDN 03 Batang Anai Kecamatan Batang Anai - Rahmi Agusti; Syahrul R; Ramalis Hakim; Budi Setiawan (International Journal of Educational Dynamics, 2019)
This study aims to improve the ability to write narratives using the constructivism approach of the fifth grade students of SDN 03 Batang Anai. The type of research used is Classroom Action Research. The population in this study were fourth grade students of SDN 03 Batang Anai, Batang Anai District. The study was conducted during the second semester of the 2018/2019 academic year. This study focused on the average score of students' ability to write narrative essays in cycles I and II. The following data presents the results of the test: The ability to write students' narrative essays in cycle 1 is the percentage of classical average obtained from the narrative structure consisting of Theme, Flow, Characterization, Background, Viewpoint of the expository narrative with an average score of 56%. Looking at the circumstances that occur as well as the classical average, the average percentage of students' ability to write narrative essays in cycle 1 is only 56%, so this is far below the indicator of success set at 75%. In the second cycle the ability to write student narrative essays is the Theme, Flow, Characterization, Background, Viewpoint of the suggestion narrative with an average score of 78%.